Pharmacogenomics Based Practice in Malaysia: The Attitude, Knowledge and Adoption by the Healthcare Professionals - Z, Bannur; S, Bahaman; MZ, Salleh; LK, Teh (IIUM Medical Journal Malaysia, 2014)
Introduction: Knowledge, attitude as well as adoption of pharmacogenomics in clinical practice among the pharmacists and physicians in Malaysia have not been reported. This cross-sectional study explores various facets of the two professions as related to pharmacogenomics to determine the need and preferred method to improve education among them. This study also aims to identify the current state of pharmacogenomics practice in Malaysia to help identify barrier and solution to reap advantages from pharmacogenomics practices. Methods: A questionnaire consisting of 38 questions in five parts was adopted and validated. It explores the respondents’ characteristics, attitude, knowledge, adoption and education. It was distributed online to 1500 pharmacists and physicians over five months. Results: Pharmacists differed from the physicians in terms of attitude, knowledge, adoption and education. Overall, adoption rate of pharmacogenomics was found to be low but its anticipation for future adoption is high, and benefits were reported by healthcare professionals who have used the test in a clinical setting. Majority of respondents had poor to fair knowledge and nearly half have had no prior formal teaching on pharmacogenomics. Interest in the education is very high, and most of them preferred to learn pharmacogenomics via continuous professional education programs. Conclusion: Pharmacogenomics is a field that promises many benefits, but to reap these benefits require its implementation in clinical setting. Pharmacists and physicians need to be equipped with adequate knowledge and positive attitude towards pharmacogenomics.